Determining the effect of heat treatment on iron fortified soybean gari blend and its potential bioavailability - Leticia Amoakoah Twum; Fidelis C.K. Ocloo; Dora Duah-Bisiw; Bernard Tawiah Odai (Scientific African, 2021)
Gari is a cassava based food product which lacks most essential nutrients needed to promote good health and growth. An easy-to-adopt strategy widely accepted and used by most low-income household to improve nutritional intake is to blend nutrient dense and nutrient-poor agricultureal produce in a meal. Soybean is used in food blends, as it contributes to caloric source especially supplementary protein. Micronutrient deficiency has been a major challenge in middle and low income countries. The most prominent of micronutrient deficiencies is iron deficiency, which has a potential harmful developmental effect especially on infants, adolescent girls, pregnant women and the elderly. Gari is widely consumed in Ghana and along the West African coast, therefore can be a good medium for food fortification to improve nutrition. The objective of the study was to fortify defatted soybean gari blend with iron and evaluate the effect of heat treatment on anti-nutrient content, estimated iron bioavailability and colour of the products. A known quantity of commercial food grade ferric sodium (FeNa) EDTA was added to cassava mash (with or without commercial food grade defatted soybean flour) before and after processing into gari. The elemental composition, anti-nutritional properties, estimated iron bioavaliability and colour of the product were determined using appropriate analytical methods. Results showed that fortification with iron improved the iron content of the gari samples (with or without defatted soybean flour). Addition of iron to defatted soybean gari blend before heat treatment significantly (p<0.05) decreased the lightness (L*) and yellowness (b*) of the end product. Blending gari with soybean flour elevated its anti-nutrient content; however the estimated molar ratios of anti-nutrients to iron and zinc contents were within acceptable levels as stipulated by USAID and FAO guidelines. Iron fortification of soybean gari blend has huge potential to reduce iron deficiency anaemia and protein-energy malnutrition among gari consumers in Africa.